PENGARUH GAYA BAHASA PENYIAR TERHADAP RATING RADIO SINAR MEGA SWARA FM (SMS) (Kasus Masyarakat Kp Cigadog Desa Tenjolaya Kecamatan Cicurug Kabupaten Sukabumi) - Aptan Sependi; Dwi Rini Sovia Firdaus; Intan Tri Kusumaningtias (Jurnal Penelitian Sosial Ilmu Komunikasi, 2020)
This study aims to determine Radio Sinar Mega Swara Fm Rating, find out the Influence of Broadcasting Languages,the pronunciation style of Radio Broadcaster,the Tone of Voice of Radio Broadcasters, and the Accentuation (emphasis on important words) Radio Broadcaster. This research usesSimple Linear Regression method and the Stimulus-organism-response (S-O-R) as the grand theory, using questionnaires to 51 respondents in the Cicurug subdistrict Sukabumi regency, precisely in Kp. Cigadog. The sampling technique uses Puposive Random Sampling, with correlation test. Validity test uses Pearson Product Moment formula and reliability test with Cronbach Alpha formula. While data processing uses IBM SPSS Statistics 20 and Microsoft Excel 2010. The results of simple linear regression equation in this study are as follows: Y = 6,305 + 0814X. Where Y is the radio rating of mega swara fm and X is the style of announcer language. The model means that every time an increas in the value of language style (X) will be followed by an increase in the radio rating (Y). Then it can be seen that from the variable X to the variable Y has an influence.  Keywords:Language Style, Announcer, Radio Rating.Chaer Abdul, A. L. (2010). Sociolinguistics:Perkenalan Awal. Jakarta: Rienika Cipta.Harley, P. (2006). Radio Penyiaran It's Not Just a Talk. Malang: Bayumedia Publishing.Irawan, S. (2008). Metode Penelitian:Suatu Teknik Penelitian Bidang Kesejahteraan Sosial dan Ilmu Sosial Lainnya. Bandung: Remaja Rosdakarya.Irwanto, d. (2002). Psikologi Umum. Jakarta: Total Grafika.Masduki. (2004). Menjadi Broadcaster Professional. Yogyakarta: Pustaka Popular LkiS.Morissan, M. (2008). Manajemen Media Penyiaran. Jakarta: Kencana Pranadamedia Group.Nurudin. (2007). Pengantar Komunikasi Massa. Jakarta: PT. Raja Grafindo Persada.Olii Hellena, L. H. (2013). Repoertase Radio dan Televisi Ed 2. Jakarta: Permata Puri Media.Rachmat, K. (2012). Komunikasi dan Regulasi Penyiaran. Jakarta: Kencana Prenada Media Group.Rahmawati Indah, D. R. (2011). Berkarier di Dunia Broadcast. Bekasi: Laskar Askara.Singarimbun Masri, S. E. (2012). Metode Penelitian Survei. Jakarta: LP3ES.Siregar Syopian, M. (2013). Statistik Parametrik Untuk Penelitian Kuantitatif. Jakarta: PT. Bumi Aksara.Sugiyono. (2011). Metode Penelitian Kuantitatif Kualitatif dan RD. Bandung: Alfabeta.Sugiyono. (2014). Statistika Untuk Penyiaran. Bandung: Alfabet